Experienced stigma and self-stigma in Chinese patients with schizophrenia. - Lv, Y; Wolf, A; Wang, X (2013)
OBJECTIVE: To investigate experienced stigma and self-stigma in patients with schizophrenia in mainland China. METHODS: Ninety-five patients with schizophrenia, enrolled between January 2011 and March 2011, completed Chinese versions of two self-report questionnaires: the Internalized Stigma of Mental Illness (ISMI) scale and the Modified Consumer Experiences of Stigma Questionnaire (MCESQ). They also completed two other self-report questionnaires: the Social Support Rating Scale (SSRS) and the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire. Patients were also assessed by a senior psychiatrist using the Scale for Assessment of Positive Symptoms (SAPS) and the Scale for Assessment of Negative Symptoms (SANS). All analyses were performed using SPSS 17.0 and included descriptive statistics, correlation analysis and multiple linear regression. RESULTS: On the ISMI, the percentage of participants who rated themselves above the mid-point of 2.5 (meaning high level of self-stigma) on subscales and overall score was 44.2% (n=42) for alienation, 14.7% (n=14) for stereotype endorsement, 25.3% (n=24) for perceived discrimination, 32.6% (n=31) for social withdrawal and 20.0% (n=19) on the overall score. On the MCESQ, the percentage of participants who rated themselves above the mid-point of 3.0 on subscales and overall score was 24.2% (n=23) for stigma, 1.1% (n=1) for discrimination and 1.1% (n=1) on the overall score. Some socioeconomic variables, but not positive or negative symptoms, were related to the severity of psychiatric stigma. CONCLUSIONS: Results document the seriousness of experienced stigma and self-stigma in persons with schizophrenia. Strategies are needed to improve how governments and persons with schizophrenia cope with stigma.